Progression of hepatitis C in the haemophiliac population in Ireland, after 30 years of infection in the pre‐DAA treatment era. Issue 5 (27th July 2017) - Murphy, N.; O'Mahony, B.; Flanagan, P.; Noone, D.; White, B.; Bergin, C.; Norris, S.; Thornton, L.; ,
Abstract : Introduction: Prior to the introduction of viral inactivation of factor concentrates and screening of blood, 225 people with haemophilia became infected with hepatitis C (HCV) in Ireland. Aim: Our aim was to assess liver disease progression and mortality in this population after 30 years of infection. Methods: Demographic and clinical data were collected from medical records in five hepatology units and one infectious disease unit retrospectively in 2005, and on four subsequent occasions. Results: The participation rate was 73% (165/225). Eighty three percent of patients, who had been tested for RNA ( n = 106/128), developed chronic HCV infection. Thirty four percent were co‐infected with HIV. All‐cause mortality, after approximately 30 years of infection with chronic HCV, was 44% in HIV positive patients and 29% in HIV negative patients. Liver‐related mortality was 12.5% and did not vary significantly by HIV status. Thirty seven percent of patients had developed advanced liver disease, including 20% with cirrhosis and 9% with hepatocellular carcinoma. In the pre‐interferon‐free direct acting antivirals era, 57% ( n = 60/106) of patients were treated for HCV, 65% of whom achieved a sustained virological response. Successfully treated patients had few adverse liver outcomes. Conclusion: After 30 years of infection, 40% of the patients who had evidence of chronic HCV had developed advanced liver disease, such as cirrhosis and HCC, or had died from liver‐related causes. This proportion is high relative to similar international cohorts despite good anti‐HCV treatment uptake and responses.